People for Peace and Republic: A Fantasy Theme Reading of the Representation of ‘Nepalis’ in Movement-Time Editorials - Kafle, Hem Raj (Molung Educational Frontier, 2022)
Newspapers’ editorializing exigencies as a mere publication of spot news would not be enough. Editorials clarify, explain, interpret, or integrate the news based on events, incidents, situations, or trends. Events of and during political movements are the main subjects of newspaper editorials. Editorial coverage of everyday exigencies builds up and helps represent narratives of various actors directly or indirectly involved in the events. In the public texts in Nepal, including newspapers, ‘Nepali people’ feature as principal actors and participants in socio-political transformations. Through Fantasy Theme Analysis of editorials on political subjects, this article explores how The Kathmandu Post and The Himalayan Times covered ‘Nepali people’ as the participants, actors, and agents of political transformation during the people’s movement in 2005-2006. The article inductively concludes that with a principal rhetorical vision for establishing peace and republic, ‘Nepali people’ performed the agency of transformation in the country.